Coordenadas de pontos GPS utilizando o código e formas de correção ionosférica e troposférica - Pereira, Rafaela Carvalho (2008)
This work was developed in a polygonal area that was established in an experimental place of Farm Liberdade, which is located in Tupantuba, a district of Santiago, RS. This research comprised a survey of a polygonal area including a GPS receptor of simple frequency in absolute mode, which aims at determining the coordinates of the vertices of an experimental area by using the code with and without corrections due to the propagation of signal through the atmosphere (troposphere and ionosphere). The different strategies of the processing of the code, which involved or not the corrections of ionosphere, used in this research were: I0 (without correction of ionosphere); I1 (with correction of ionosphere from the pseudo-distances PL1 and PL2); and I2 (with correction of ionosphere by the Klobuchar model). The different strategies of the processing of the code, which involved or not the corrections of troposphere, used in this research were: T0 (without correction of troposphere); T1 (with correction of troposphere by the Hopfield model); T2 (with correction of troposphere by Saastamoinen model); and T3 (with correction of ionosphere by Marini model). The values of the coordinates of the vertices from the polygonal area, which were obtained in the absolute positioning mode, considering different ways of correction of the ionospheric and tropospheric errors, were compared to the values of the coordinates of the vertices from the polygonal area obtained by the processing in the relative mode and considering the bearer phase (testimony) as being observable. In order to accomplish this comparison, it was realized the analysis of the regression among the values of the coordinates from the polygonal waypoints, which were obtained through different procedures that aimed at achieving the correlation coefficient (r), the Wilmont index of concordance (c) and the level of development of the strategy that was taken into consideration. Due to the analysis of the results, it was possible to conclude that there was no difference in the performance of the different strategies of corrections of errors. Furthermore, the positioning error is about 5m due to the propagation of the signal through the atmosphere when the absolute positioning mode is used.